THE ROOTS OF MERARIK TRADITION: From Resistance To Acculturation - Faizin, Khairul (STAI Darul Kamal NW Kembang Kerang, 2020)
This paper describes the origin of the Sasak-Lombok tribe's tradition of pulling which is based on oral folklore. The roots of this tradition can be traced back to the history of the 17th century Lombok-Bali meeting. In general, there are four views about the roots of the formation of the Sasak tribe tradition of drawing. The four views are First, pulling is a traditional Sasak norm; The second merarik is a resistance to the shackles of the triwangsa social strata; The third merarik is the release of Sasak women from the kidnapping of Balinese Buleleng soldiers; The fourth line is the acculturation of Balinese culture.